Cell-Extrinsic Defective Lymphocyte Development in Lmna(-/-) Mice - Hale, J. Scott (Public Library of Science, 2010)
BACKGROUND: Mutations in the LMNA gene, which encodes all A-type lamins, result in a variety of human diseases termed laminopathies. Lmna(-/-) mice appear normal at birth but become runted as early as 2 weeks of age and develop multiple tissue defects that mimic some aspects of human laminopathies. Lmna(-/-) mice also display smaller spleens and thymuses. In this study, we investigated whether altered lymphoid organ sizes are correlated with specific defects in lymphocyte development. PRINCIPAL FINDINGS: Lmna(-/-) mice displayed severe age-dependent defects in T and B cell development which coincided with runting. Lmna(-/-) bone marrow reconstituted normal T and B cell development in irradiated wild-type recipients, driving generation of functional and self-MHC restricted CD4(+) and CD8(+) T cells. Transplantation of Lmna(-/-) neonatal thymus lobes into syngeneic wild-type recipients resulted in good engraftment of thymic tissue and normal thymocyte development. CONCLUSIONS: Collectively, these data demonstrate that the severe defects in lymphocyte development that characterize Lmna(-/-) mice do not result directly from the loss of A-type lamin function in lymphocytes or thymic stroma. Instead, the immune defects in Lmna (-/-) mice likely reflect indirect damage, perhaps resulting from prolonged stress due to the striated muscle dystrophies that occur in these mice.